The Public Domain vs. the Museum: The Limits of Copyright and Reproductions of Two-dimensional Works of Art. Issue 1 (28th August 2014) - Petri, Grischka
The problem of museums and public institutions handling reproductions of works in their collections is not only a legal question but also one of museum ethics. Public museums are committed to spreading knowledge and to making their collections accessible. When it comes to images of their holdings, however, they often follow a restrictive policy. Even for works in the public domain they claim copyright for their reproductive photographs. This paper offers an analysis of the different interests at stake, a short survey of important cases, and practical recommendations.